Efforts to Emphasize the Poor Population and the Affecting Factors - Sihombing, Imran Setiabudi (Advances in Social Sciences Research Journal, 2019)
This study aims to determine the effect of economic growth, human development index and unemployment rate to suppress the number of poor people in North Sumatra Province for the period of 2013-2017. The data used in this study is secondary data from the publication of statistical data by Badan Pusat Statistik (Central Statistics Agency) of North Sumatra Province. These data are tabulated into a panel data structure, which is a combination of data in the form of time series and cross-section. This study uses data from 33 Regencies / Cities in North Sumatra Province to be analyzed by using the Data Panel Regression Analysis technique with the Fixed Effect approach. Empirical results prove that economic growth variables on poverty have a positive and significant effect, while the human development index and unemployment variables have insignificant effects. These data were tabulated into a panel data structure, which is a combination of data in the form of time series and cross-section. This study uses data from 33 Regencies / Cities in North Sumatra Province to be analyzed by using the Data Panel Regression Analysis technique with the Fixed Effect approach. Empirical results prove that economic growth variables on poverty have a positive and significant effect, while the human development index and unemployment variables have insignificant effects.